Placental Cryoextract and Renin-Angiotensin-Aldosterone System Blockade Mitigate Renal Failure in Rats - Repin , Mykola; Chyzh , Yuliia; Marchenko, Larysa; Tetyana P. Govorukha, Tetyana P. Govorukha; Brusentsov, Oleksandr (Problems of Cryobiology and Cryomedicine, 2021)
Here, we have studied the impact of administration of rat placental cryoextract (PCE), drug blockade of the renin-angiotensin-aldosterone system (RAAS) with enalapril and spironolactone and their combination on the rat kidney tissue structure and excretory function at different stages of chronic renal failure (CRF) development using the glycerol model. In 3 weeks after glycerol introduction, the animals from all the groups showed low values of glomerular filtration rate, impaired blood flow in renal cortex, tubular epithelial dystrophy, inflammation and edema of interstitium, indicating the onset of CRF development. Tubulo-interstitial nephritis and nephrosclerosis were dominated in untreated rats 16 weeks later. The use of RAAS drug blockade, as well as a comprehensive therapy with RAAS blockers and placental cryoextract stopped the inflammatory processes in renal tissue, restored blood circulation and normalized excretory function, which persisted for up to 16 weeks of observation. Probl Cryobiol Cryomed 2021; 31(3): 223–235